Developing a building sustainability assessment model for the South African built environment : searching for new appoaches to improve the effectiveness of building assessment - Kaatz, Ewelina (Department of Construction Economics and Management, 2019)
The fundamental premise of research presented in this thesis is the search for conceptual approaches and practical measures to enhance the practice of building assessment in fostering sustainable construction. Hence, this thesis advances the theory for the practice of building assessment that incorporates the principles of sustainable development. The research findings are communicated via a functional specification for a building sustainability assessment model, suitable to the South African context. The research focuses primarily on process-related aspects of building assessment. Important insights for the development of the model's specification are gained from the review of the practice and experience of Environmental Assessment (EA) in addressing sustainability at a project level. Lessons are also drawn from the Process Protocol (PP), which provides a means of describing the building project process in a way that is transparent and accessible to building stakeholders. The most relevant insights sourced from these two fields of expertise are grouped into three key themes. These include integration (i.e. integration of sustainability principles, stakeholder values and perspectives), transparency and accessibility (i.e. open participation and communication competence) and collaborative learning (i.e. active involvement and transfer of knowledge). It is proposed that these themes form key outcomes of building assessment and be viewed as crucial functionalities of the model. The model is presented as a generic method that can be customised to suit the context of its application. The potential use scenarios of the model, identified in this thesis, include the formulation of a building project proposal, a building project sustainability appraisal and a building performance audit. The use of process maps produced through this research facilitates the identification of interfaces between the model and the building process in terms of decision-points and associated information needs in each use scenario. The model's user personas are also discussed (i.e. building stakeholders) with regard to the potential benefits and challenges of their participation in the building assessment process. The theory for building assessment advanced in this thesis was validated during a workshop with South African academics and built environment practitioners, held at the University of Cape Town. The thesis concludes that building assessment methods can do more than assess the sustainability of a building. More importantly, they provide a means of introducing the principles of sustainable development into the processes that produce the built end-product. This suggests a need to move beyond the terminology of building assessment and instead talk of enhancement models that would facilitate a shift in the practice of building assessment from measuring to one of proactive improvement.